Comparison of Sex Differences in Outcomes of Patients With Aneurysmal Subarachnoid Hemorrhage: A Single-Center Retrospective Study - Cai, Yuankun; Liu, Zheng; Jia, Chenguang; Zhao, Jingwei; Chai, Songshan; Li, Zhengwei; Xu, Chengshi; Zhang, Tingbao; Ma, Yihui; Ma, Chao; Chen, Xinjun; Jiang, Pucha; et al. (Frontiers in Neurology, 2022)
Background: Although female present differently from male patients in total stroke, gender differences in outcome of patients with aneurysmal subarachnoid hemorrhage (aSAH) remain controversial. The aim of this study was to compare the gender differences in outcome of patients with aSAH. Method: This study retrospectively analyzed the clinical data of consecutive patients with aSAH admitted to the Department of Neurosurgery, Wuhan University Zhongnan Hospital from May 1, 2020 to December 31, 2020. The modified Rankin Scale (mRS) score was used to evaluate the prognosis of patients at discharge. Outcome indicators include cerebral ischemia, hydrocephalus, and mRS scores ≥2 at discharge. Results: A female (65%) majority of 287 patients with aSAH were included in the study. Patients were divided into female (n=184) and male groups (n=99) according to gender, and female patients were significantly older than males (61.3±8.5 vs. 60.0±8.5, p=0.032). The incidence of comorbidities (hypertension, diabetes and heart disease) was higher in female patients than in males, but the difference was not statistically significant. Although more female than male patients underwent endovascular treatment, there was no statistical difference in the treatment approach between the two groups. Comparison of postoperative complications and mRS scores at discharge between male and female patients revealed that the rate of cerebral ischemia and mRS ≥2 points at discharge was significantly higher in female patients than male. And, this difference persisted after propensity adjustment for age and treatment approach in both groups. Analysis of risk factors for poor prognosis at discharge in both pre- and post-adjustment patients showed cerebral ischemic and high mFisher score (mFisher =3/4) as independent risk factors. Conclusion: Female with aSAH have a worse prognosis compared to men, and this difference may be related to the fact that the female is more susceptible to cerebral ischemic.